Modulation of New Excitons in Transition Metal Dichalcogenide‐Perovskite Oxide System. Issue 12 (29th April 2019) - Yin, Xinmao; Yang, Ming; Tang, Chi Sin; Wang, Qixing; Xu, Lei; Wu, Jing; Trevisanutto, Paolo Emilio; Zeng, Shengwei; Chin, Xin Yu; Asmara, Teguh Citra; Feng, Yuan Ping; Ariando, Ariando; et al.
Abstract: The exciton, a quasi‐particle that creates a bound state of an electron and a hole, is typically found in semiconductors. It has attracted major attention in the context of both fundamental science and practical applications. Transition metal dichalcogenides (TMDs) are a new class of 2D materials that include direct band‐gap semiconductors with strong spin–orbit coupling and many‐body interactions. Manipulating new excitons in semiconducting TMDs could generate a novel means of application in nanodevices. Here, the observation of high‐energy excitonic peaks in the monolayer‐MoS2 on a SrTiO3 heterointerface generated by a new complex mechanism is reported, based on a comprehensive study that comprises temperature‐dependent optical spectroscopies and first‐principles calculations. The appearance of these excitons is attributed to the change in many‐body interactions that occurs alongside the interfacial orbital hybridization and spin–orbit coupling brought about by the excitonic effect propagated from the substrate. This has further led to the formation of a Fermi‐surface feature at the interface. The results provide an atomic‐scale understanding of the heterointerface between monolayer‐TMDs and perovskite oxide and highlight the importance of spin–orbit–charge–lattice coupling on the intrinsic properties of atomic‐layer heterostructures, which open up a way to manipulate the excitonic effects in monolayer TMDs via an interfacial system. Abstract : The observation of high‐energy excitons generated by a mechanism in monolayer‐MoS2 on SrTiO3 is reported, which are attributed to the change in many‐body interactions that couples with interfacial orbital‐hybridization. This has further led to a fermi‐surface feature at the interface. The results provide an atomic‐scale understanding of two‐dimentional heterointerfaces and shows the crucial role that the many‐body interactions play.